Digital Transformation of CRM and Transition to e–CRM - Ruskov, Plamen; Boevsky, Ivan (Economy and Business Yearbook, 2022)
The last two decades of the previous century and the first two decades of the current century enabled CRM to become ubiquitous in both global companies and small businesses. This process continues and changes. With this paper work we aim to identify and illuminate this transformation, which we identify as the transition from CRM to e-CRM. Therefore, at the beginning, we characterize the key concepts for the development, then discuss the similarities and differences between digitalization, digitization and digital transformation. We continue with an analysis of digital transformation and its main principles and processes. Here we emphasize, in parallel with many other transformations in the corporation/ organization, and on the need for it to become an “agile organization” and to adapt its specific digital culture. In this regard, we compare the features and identify the similarities and differences between CRM to e-CRM. To illuminate all this, we use case studies of companies - leaders in digital transformation and e-CRM. Finally, we end with a conclusion in which we focus on the need to run the digital transformation process in parallel with the digital adaptation process of the company/ organization.